2020
DOI: 10.1002/1873-3468.13747
|View full text |Cite
|
Sign up to set email alerts
|

Digital magic, or the dark arts of the 21stcentury—how can journals and peer reviewers detect manuscripts and publications from paper mills?

Abstract: In recent years, it has been proposed that unrealistic requirements for academics and medical doctors to publish in scientific journals, combined with monetary publication rewards, have led to forms of contract cheating offered by organizations known as paper mills. Paper mills are alleged to offer products ranging from research data through to ghostwritten fraudulent or fabricated manuscripts and submission services. While paper mill operations remain poorly understood, it seems likely that paper mills need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
93
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 24 publications
0
93
0
3
Order By: Relevance
“…A third party provided the same results to two research teams, and the articles of both teams solved the same research questions and reported the same data, results, and conclusions (29). Recent investigations have suggested the presence of paper mills (30). They use manuscript templates to produce a lot of similar articles, regular and similar results pictures, and submit these articles to various journals for his client.…”
Section: Resultsmentioning
confidence: 99%
“…A third party provided the same results to two research teams, and the articles of both teams solved the same research questions and reported the same data, results, and conclusions (29). Recent investigations have suggested the presence of paper mills (30). They use manuscript templates to produce a lot of similar articles, regular and similar results pictures, and submit these articles to various journals for his client.…”
Section: Resultsmentioning
confidence: 99%
“…Within this backdrop, the issue of paper mills, 3 which are paid services that provide made-to-order “scientific papers”, data, ghost-writing or other suspect services that give academics unfair gains, for a price, needs to be emphasized. When an individual orders data from a paper mill, for example a data set or a figure (graph, plot, etc.…”
mentioning
confidence: 99%
“…In the worst-case scenarios, radical elements that have benefitted or profited from paper mills should face criminalization. 5 Editors and journals that were genuinely unwittingly victimized, and blind-sighted by the elaborate ability of dishonest authors to defraud them, should consider investing in forensic image software 3 because such journals have become “soft targets”.…”
mentioning
confidence: 99%
“…The emerging truth from these community efforts is uncomfortable; it appears that misconduct when publishing scientific research runs much deeper than the occasional ‘sting’ operation. Moreover, it appears that fabricated research papers are readily available for purchase by scientists driven by the need to publish more papers to further their careers (see Byrne and Christopher, 2020 ).…”
mentioning
confidence: 99%
“…Figures within accepted articles are checked by trained in-house production staff for evidence of image manipulation. Byrne and Christopher ( Byrne and Christopher, 2020 ) have identified two types of fraudulent images: invented images and stock images. Invented images are typically western blots, and might include placing individual bands onto false backgrounds, non-linear adjustments, the splicing of multiple images to suggest they come from the same gel, duplicated bands and lanes, and grouping or consolidation of the data (e.g.…”
mentioning
confidence: 99%